User-Generated Fashion Visuals as Informal Infographics: and Emotional Engagement in Generations Y and Z - García Medina, Irene; Rodríguez-Blanco, Sergio; Ortega Fernandez, Eglee (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This study examines how digital fashion visuals on websites and apps influence the purchasing behaviour of Generations Y and Z. Using the AIDA model (Attention, Interest, Desire, Action), it tracks the consumer journey from social media to brand platforms and identifies six key interpretive dimensions. It introduces the concept of informal infographic—non-standardized, often user-generated visuals that clarify complex information. Through a mixed-methods design (survey n=121; interviews n=8), findings show that clarity, realism, and context enhance emotional and cognitive engagement. The main contribution is expanding infographic theory to include user-generated fashion content as epistemic tools in e-commerce.